Problematyka sytuacji społecznej homoseksualnych kobiet jako potencjał do zastosowania badań eklektycznych - Dziarnowska, Marta (Kultura-Społeczeństwo-Edukacja, 2020)
Scientists practicing social sciences issues more and more often undertake constructing and performing eclectic research projects. Nowadays, qualitative and quantitative approaches are thought to be equivalent. Their results can be characterized by complementarity, facilitation and/or triangulation. The article presents two research papers – quantitative which is represented by a report titled ‘Social situation of LGBTA people in Poland. Report 2015-2016’ written by organizations supporting LGBTQIA environments – and quantitative master thesis titled ‘The quality of life of homosexual women – cases study’. These projects arose in similar time, but they were developed and conducted independently. Compared results are connected to issues of functioning of homosexual women in a range of identical or approximate categories of both studies. The main aim of the article is to show the validity of quantitative and qualitative trends connection on the example of presented papers – despite of distinctiveness of these two conceptions their results illustrate each other in many questions. The quantitative publication pictures the scale of the phenomenon while the qualitative one gives the context of gathered data. In presented text it is shown not only how the results complement one another, but also how they mutually verify and give a possibility to widen the cafeteria of dependent variables or categories of thematic-notions frame. The secondary aim of the paper is to outline the problematic aspects of functioning of homosexual women in environments and social groups to which they belong. The article is rich in references that discusses in details mentioned issues; these are: an attitude toward public institutions and condipolitics in Poland, conditions of sexual orientation openness, professional, family and social relations, same-sex relationships and a violence motivated by prejudices. The awareness of benefits from using the eclectic approach in examining social phenomena can arise the cognitive value of research projects and as an effect increase effectiveness of actions in favour of nonheteronormative individuals.